A Longitudinal Examination of the Asthma Medication Ratio in Children with Medicaid. (2nd October 2020) - Andrews, Annie Lintzenich; Brinton, Daniel L.; Simpson, Kit N.; Simpson, Annie N.
Abstract: Background/Objective: An efficient and accurate strategy for identifying children with asthma at high-risk for exacerbation is needed. The objective of this study is to conduct a longitudinal examination of the asthma medication ratio (AMR) (#of controller medication claims/(# of controller medication claims + # of rescue medication claims)) in Medicaid-funded children with asthma. This measure has the potential to be a near real-time risk assessment tool. Methods: We conducted a retrospective analysis of 2013–2014 Truven Health Medicaid data. We analyzed pharmacy and medical claims for a cohort of children with asthma. We identified patients age 2–17 years with at least one claim for an inhaled corticosteroid. We calculated an AMR for rolling 3-month periods and examined the proportion who were classified as low risk (AMR ≥ .5), high-risk (AMR < .5) and no medication claims (no asthma medication claims). Using logistic regression, we tested how the AMR predicted severe exacerbations. Results: 214, 452 eligible children were identified. The mean age is 7.8 years. 8–9% had a high-risk AMR in any given period. High-risk AMR is associated with increased odds of a severe exacerbation in the subsequent 3 months (compared to all other children) (OR 1.7–1.9 depending on time period evaluated). Conclusions: In this analysis of Medicaid-insured children with asthma, we found that the AMR is a reliable predictor of exacerbations. This will inform the development of an AMR-based risk assessment and communication intervention.